Transmission Pathway of Enterobacteriaceae from Reared Fish and Surrounding Environment to Water Body in Batang Ai Reservoir, Sarawak - Samantha Valarie Furzanne, Jamie (2021)
Batang Ai reservoir, located in Lubok Antu district, Sarawak, is a man-made lake for the purpose of electrical power generation by Batang Ai hydroelectric station. Over time, the area is developed and now the lake is surrounded by various human activities such as farming, eco-tourism, aquaculture and recreational activities, which means increasing human exposure to the lake water. The bacterial family Enterobacteriaceae is known to be ubiquitous in nature and most studies concerning Enterobacteriaceae revolves around its epidemiology, pathogenesis and anti-microbial resistance (AMR). To date, there has been no reported study on the characteristics of Enterobacteriaceae in Batang Ai reservoir. This study aimed to determine the genetic distribution and characteristics associated with AMR of Enterobacteriaceae in Batang Ai reservoir and the possible sources of Enterobacteriaceae in the lake water. Surface water samples were collected from 27 sampling points scattered around Batang Ai reservoir while four fish samples were obtained from an aquaculture farm located near the communal jetty. The presence of human activities near each sampling point were observed and recorded. The samples were transported to the laboratory in ice box containing ice for further analysis. Preliminary selection was done by plating the samples on Violet Red Bile agar (VRBA) plates, a selective media for Enterobacteriaceae and a total of 141 isolates were randomly selected from the culture plates. These isolates were subjected to DNA extraction by using the Boil Cell method with slight modifications. (GTG)5 DNA fingerprinting was carried out by using the the DNA extract to determine the phylogeny of the isolates and identified by using 16S rDNA sequencing. Five genera of Enterobacteriaceae were identified which are Enterobacter, Escherichia, Shigella, Klebsiella and Pseudocitrobacter, consisting of 12 identified species of Enterobacteriaceae, namely E. hormaechei, E. hormaechei subsp. xiangfangensis, E. cloacae, E. cloacae subsp. dissolvens, E. kobei, E. tabaci, S. boydii, S. flexneri, P. faecalis, E. fergusonii, E. coli and K, pneumoniae. Isolates belonging to the genus Enterobacter made up 29% of the total number of isolates obtained from the area, making it the most prominent genus found in Batang Ai lake. A total of 14 antibiotics from seven anti-microbial classes which are penicillins, cephems, monobactams, aminoglycosides, tetracyclines, quinolones and fluoroquinolones, and phenicols were used to determine the AMR of the isolates. A total of seven species isolates were found to have MAR index below 0.2, which is considered to be the safe level of AMR in bacteria. With the exception of ampicillin and tetracycline, all antibiotics have 25% or less bacterial species displaying resistance. Most of the bacterial species showed resistance towards ampicillin which is 75%. E. fergusonii, S. flexneri and K. pneumoniae, which were isolated from water samples obtained near the aquaculture farm, communal jetty and also fish samples, have a MAR index of 0.5, 0.375 and 0.214 each. It was suspected that the addition of antibiotics to the fish fees used at the aquaculture farms caused the species found in this area to develop AMR. This poses the risk of antibiotic-resistant bacterial infections towards the surrounding community through water-related activities such as traveling via water transportation and also through the consumption of reared fish harboring aforementioned species. In conclusion, t was proven that Enterobacteriaceae are transmitted to the reservoir through aquaculture farming, littering, traditional farming and planting sites happening in the area, thus is was proposed that a guideline for activities to be carried around the area is created and imposed.